Effects of drawdown scenario on retrogressive lateral erosion in a reservoir. (18th October 2022) - Artruc, Tessa; Tullos, Desiree; Leshchinsky, Ben
Abstract: The drawdown of reservoirs behind dams is an important management strategy (e.g., for removal of aging infrastructure, flushing of sediment), and an opportunity to study erosional processes. A numerical model was developed to examine retrogressive bank erosion across reservoir drawdown scenarios and to evaluate factors controlling the rate, volume, and mechanisms of lateral erosion. Modeled processes included dynamic drawdown of groundwater, sequential slope failures via limit equilibrium analysis, and retrogression considering stress interaction between failing blocks. Field measurements were coupled with Staged, Slow, and Rapid drawdown scenarios. Results highlight the importance of including retrogression as an avenue for lateral erosion, as sequential block failures were found to occur in all scenarios except Slow drawdown. This result indicates that bank stability models without some means of characterizing the evolution of slope failure during drawdown are likely underestimating bank failure rates and volumes. In contrast, dynamic groundwater was not found to be a dominant control for any drawdown scenario. Model results also demonstrate that the drawdown increment is a first‐order control on slope instability via the development of drained or undrained conditions. A majority of failures occurred under undrained conditions. To maximize slope stability, using slow drawdown to activate internal friction under drained conditions is essential. The design of the drawdown rate created a tradeoff between the amount of impact created and when the impact is produced. The study also articulated the need for coupling models and field observations for rapidly changing systems.